THE VALUE OF NATIONAL PLURALITY IN THE DESIGN OF THE CONSTITUTIONAL STATE - del Real Alcala, Juan Alberto (European Scientific Journal, ESJ, 2013)
The constitutional changes that are taking place in Latin America have meant, for many of these countries, a profound reform (or, sometimes, rupture) in the “Model of Constitutional State” that sustains their democratic systems. 19th century Legislative State (legalism as a legal theory), whose applicability practically extended to the 20th century and beyond, is being substituted on the whole by a Constitutional State configured in the paradigm of neo-constitutionalism, a prototype that we modern democracies are currently operating within. This is the case for Bolivia, wherein the 2009 Constitution established a “Plurinational Constitutional State”, with all of the implications that this has meant for the design of the institutional aspect of the country.